The Spiritualist Movement: Speaking with the Dead in America and Around the World edited by C. M. Moreman - Evrard, Renaud (Journal of Scientific Exploration, 2014)
<!--[if gte mso 9]> 14.00 <![endif]--> Christopher M. Moreman, Associate Professor in the Department of Philosophy at the University of East Bay, edited this three-volume anthology comprising 43 chapters contributed by as many authors. Each of the three volumes is divided into three or four sections, with two to eight thematically grouped chapters. Each volume is separately indexed. Photographs, tables, and other relevant illustrations are provided in limited numbers. The initial impetus for this project came from the work of the "Death, Dying, and Beyond program unit" at the American Academy of Religion, established in 2004 by Moreman. He tried to focus on Spiritualism as a specific religious movement, "not to be confused with general spirituality or with mediumship in a broader global and historical context" (Volume 1:x). Defined as such, Spiritualism is a relatively young movement that appeared in the mid-nineteenth century in America and rapidly developed worldwide. There has not been such a large analysis of the worldwide Spiritualist movement since Sir Arthur Conan Doyle's two-volume The History of Spiritualism, first published in 1926, and recently reedited in French (Doyle 2014). But Moreman's anthology affords a scholarly approach to this topic without any attempt to persuade of the correctness or wrongness of spiritualist doctrines. Even as Spiritualism has remained popular, it received relatively little academic attention: Such an anthology recognizes the lacuna and tries to rectify it. By doing so, it also contributes to a better understanding of all related areas, including scientific approaches to spiritualistic phenomena. <!--[if gte mso 9]> Normal 0 false false false FR JA X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Cambria","serif"; mso-ascii-font-family:Cambria; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Cambria; mso-hansi-theme-font:minor-latin; mso-ansi-language:FR; mso-fareast-language:JA;} --> <!--[endif] -->